How would I answer this question? Use factor theorem to show (x-2) is a factor of f(x) = 2x^3 -7x^2 +4x +4.

The first step is to find out the value of x for which your bracket/value you think is a factor equals 0. So, x – 2 = 0, therefore x = 2. Now plug in this value into your original equation and if the result is 0, your bracket is a factor. So f(2) = 2(2^3) – 7 (2^2) +4(2) +4 = (28) – (74) + 8 + 4 = 16 – 28 + 12 = 0. Therefore (x-2) is a factor.

Answered by Maria S. Maths tutor

3961 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Show that the cubic function f(x) = x^3 - 7x - 6 has a root x = -1 and hence factorise it fully.


Can you please explain how to expand two brackets, eg. (3x-7)(5x+6)


Line AB, with equation: 3x + 2y - 1 = 0, intersects line CD, with equation 4x - 6y -10 = 0. Find the point, P, where the two lines intersect.


Find the exact solution of the following equation: e^(4x-3) = 11


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences